Euler Integrals and Their Applications - Parvina Mahmadamin qizi Ulasheva; Javlon Mardonov (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study examines the theoretical foundations and practical applications of Euler integrals, focusing on their role in modern mathematical analysis. Special attention is given to the Gamma and Beta functions as fundamental representations of Euler integrals. The research explores their properties, interrelationships, and effectiveness in solving complex integrals and differential equations. Additionally, the study highlights their applications in physics, engineering, and probability theory. The results demonstrate that Euler integrals serve as a crucial link between theoretical concepts and real-world problem-solving, making them indispensable in both scientific research and applied fields.